Structural and optical study of electrodeposited CuSe thin films. (2021) - Malekar, V.P.; Gangawane, S.A.; Fulari, V.J.
Abstract: The CuSe thin films are prepared by Electrodeposition method. The structural and optical properties of CuSe thin films are studied by means X-Ray diffraction (XRD) study, Scanning Electron Microscopy (SEM), and UV–Visible absorption study. Optical absorption study is carried out using UV–VIS spectrometer in the wavelength range 350–850 nm of electrodeposited CuSe thin films deposited on FTO coated glass substrate. The optical band gap energy of CuSe thin film varies from 2.4 to 2.6 eV. It has been observed that the electrodeposited films are polycrystalline in nature. Also, it is evident that band gap energy increases by decreasing bath concentration as well as deposition time.